Effectiveness of Reference Height Control system for Tripod Hopping Robot - Anuar , Mohamed Kassim; Mohammad Fahmi , Miskon; Nurul Hafizah, Abd Rahim; Takashi , Yasuno (2011)
In this paper, the generation of vertical jumping motion for tripod hopping robot through reference height control system method in order to converge the differences of reference height for each leg of tripod hopping robot is discussed. The proposed control system is designed using MATLAB/ Simulink which is consisted of maximum height detector, PI controller system in the system of Central Pattern Generator (CPG). By using the approached method, tripod hopping robot can maintain the hopping motion and control the jumping height to achieve the reference height. As the result, we evaluate the effectiveness of CPG networks to keep the stability of tripod hopping robot besides of confirm the validity of using reference height control system to generate moving capability at different reference height.